Evaluasi Kesesuaian Lahan untuk Tanaman Mulato (Brachiaria hybrid cv. Mulato) pada Tiga Lokasi yang Berbeda - Ferdy Firmansyah; Rija Sudirja; Apong Sandrawati; Mahfud Arifin; Iin Susilawati (Soilrens, 2022)
The objective of this research is to evaluate actual and potential land suitability of mulato grass (Brachiaria hybrid cv. Mulato) as forage crop at Dago Dairy Lembang, UPBS Pangalengan and UPBS’s field at Cipunagara. The research is qualitative descriptive research with survey that the data taken from the field and supported by laboratory analysis. Soil sampling carried out by composite sampling method with diagonal systhematic pattern. Land quality obtained from land observation and laboratory analysis compared with mulato’s land suitability criteria to obtain the land suitability level. The actual land suitability level of mulato grass were about S2 (moderately suitable) to S3 (marginally suitable) at Dago Dairy’s field, S2 and S3 at UPBS Pangalengan’s field, S2, S3 and N (non-suitable) at UPBS’s field at Cipunagara. Limiting factors found were oxygen availability (oa), nutrient retention ability (nr), nutrient availability (na) and erosion hazard (eh). Each limiting factor fixed by soil drainage, calcium carbonate or sulfur application, fertilization and cover crop cultivation. Potential suitability of mulato grass after improvement were S1 to S2 at Dago Dairy, S1 to S2 at UPBS Pangalengan and S1, S2 to S3 at UPBS’s land at Cipunagara.